(untitled) (Raparin Journal of Humanities (RJH), 2023)
This research is in titled (Intertextuality in Qubadi Jalizadah’s Poetic Texts) it’s an attempt to introduce concepts, terms, and the significance of Intertextuality in literary texts. Therefore, intertextuality is an obvious feature of a text. Thus, no text is a separate and independent realm, except the other texts. However, every text is in dialectical contact with other texts. On the other hand, it opens doors towards dialogic among texts. In the meantime, intertextuality displays the level of awareness and creativity of the writer, and to what extent they have an intellectual, cultural, and philosophical background. The aim of this research is to show and identify the types of intertextualities in the poet’s poems, in accordance with the applicable Mechanism and regulations of intertextuality, including "quotation, borrowing, and dialogic". In this study, a descriptive-analysis method has been followed. The results of the study show that the poet has benefited greatly from global and national thought and culture. From this standpoint, many types of intertextualities can be noticed in his poems, in the form of textual images (self, historical, cultural, poems of other poets, and religious) in a way that he has been able to rewrite new and vivid poetic texts and take the world of his poems further forward.